The Gut Microbiome in Pediatric Allogeneic Hematopoietic Stem Cell Transplant Patients. (4th October 2017) - Padhye, Amruta; Wylie, Kristine; Shenoy, Shalini; Mihindukulasuriya, Kusal; Storch, Gregory
Abstract: Background: Studies in adult allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients demonstrate 1) domination by certain taxa correlates with subsequent bacteremia and 2) diversity at engraftment is an independent predictor of mortality. In limited pediatric literature, one study of 10 patients showed higher relative abundance of Bacteroidetes in pre-HSCT samples in patients without acute graft vs. host disease (aGVHD). In this study we explore the post-HSCT gut microbiome in patients receiving myeloablative (MA) vs. reduced intensity (RIC) pre-transplant conditioning regimens. Methods: 119 fecal specimens were collected from 17 patients at start of conditioning, 2 weeks post-transplant, monthly and with fever or infection episodes until 6 mo. Bacterial communities were characterized by sequencing the V4 region of the bacterial 16S rRNA gene using Illumina Miseq. Bacterial density was estimated by 16S rRNA gene copy number measured by qPCR. Results: Patient characteristics included median age 9.7 years (0.3 to 20.5), females 53%, first time transplant 70%, matched unrelated donors 70% and bone marrow stem cells 70%. 10 patients (8 with malignancy) received MA regimen and 7 with non-malignant diagnoses received RIC. Outcomes included aGVHD in First year in 6 (35%), chronic GVHD in 4 (28%) survivors past 6 mo and 12 (70%) patients surviving to one year. Fever or infection episodes in First 6 mo occurred at median 2 episodes (1 to 7) including 8 bacteremia episodes, with intestinal domination preceding two ( E cloacae and E fecalis ). There was a significant decrease in bacterial density in engraftment samples compared with pre-transplant samples (median 9.9 E+7 copies (cp)/mg of stool vs. 7.6 E+8 cp/mg, P = 0.008). Bacterial density was significantly lower (1.1E+5 cp/mg vs. 2.6E+8 cp/mg, P = 0.007) and Bacteroidetes domination (>30% of taxa in a sample) less common in engraftment samples of patients with aGVHD compared with those without aGVHD. Conclusion: Allo-HSCT is associated with disruption of intestinal flora in pediatric patients. Dominance of the gut microbiota by a specific taxon may be associated with bacteremia with that organism. In preliminary analysis, bacterial density was lower and Bacteroidetes domination was less frequent in patients with aGVHD. Disclosures: All authors: No reported disclosures.